PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Ramadani, Sagita (Departemen Matematika, 2023)
One of the core mathematical talents is the ability to solve problems. Children still struggle to solve math problems in practice, though. One solution to this is to use the Geogebra-assisted Problem Based Learning methodology. The goal of this study was to find out whether students in grade VIII at SMP Negeri 13 Padang who used Problem Based Learning with Geogebra performed better on arithmetic problems than those who utilized direct learning. With a control group that merely obtains a non-equivalent posttest, this kind of research is a pseudo-experiment. The research population was composed of classes VIII.2 and VIII.5, which served as the experimental and control groups, respectively. An assessment of one's aptitude for solving mathematical problems served as a research tool. To assess the hypothesis, use the t-test. The study's findings and data analysis led to the conclusion that students in grade VIII at SMP Negeri 13 Padang who were taught using the Problem Based Learning learning model with Geogebra had superior mathematical problem-solving abilities compared to those who were taught using the direct learning model.Keywords – Problem Based Learning, Geogebra, Mathmatical Problem Solving Ability.